The collapse of the Venezuelan oil industry: The role of above-ground risks limiting foreign investment. (August 2021) - Monaldi, Francisco; Hernández, Igor; La Rosa Reyes, José
Abstract: This paper examines the role of foreign direct investment (FDI) in expanding the Venezuelan oil industry in the 1990s, the drivers leading to the expropriations the following decade, and the obstacles to attracting new investments afterward. We argue that operational control by private companies, an attractive fiscal regime, and investor protection clauses were crucial elements in fostering the expansion of the oil industry after the oil opening in the 1990s. However, a successful investment cycle adding production and reserves, combined with an oil price boom, provided strong incentives for the government to increase taxes and expropriate projects. Weak institutions, policy instability, and the lack of credible property rights for the sector generated high "above ground risks" inhibiting FDI during the oil boom, despite the massive resource base and the substantial number of deals signed. FDI underperformance contributed to the decline of the Venezuelan oil industry, even before the imposition of U.S. sanctions. Using project-level data, and industry indicators, we document how volatile fiscal terms, changes in contract governance, discretionary policies, poor operating conditions, and the lack of investor protection, explain the failure to attract FDI. Highlights: FDI in the Venezuelan oil sector went through different phases over the last 30 years. Oil prices, sunk costs, and lack of progressivity in the fiscal system help explain expropriations in 2006/2007. Weak institutions and policy instability created "above ground risks" that help explain the failure to attract FDI.